2000
DOI: 10.1177/01939450022044269
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Stress, and Depression among Russian Immigrants to Israel

Abstract: This article reports the relationships between resilience, demographic characteristics, immigration demands, and depression in a sample of 450 adult Russian immigrants to Israel. Contrary to theories of how resilience is related to psychological outcomes, no support was found for resilience modifying or mediating the relationship between the demands of immigration and depression. Resilience did, however, increase the risk of not being depressed by about two-fold (p < .0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 45 publications
3
81
0
1
Order By: Relevance
“…Nonetheless, the interaction hy pothesis regarding resilience factors was not confirmed and all of the interactions, with one exception, were not significant. Similarly, a previous study conducted among Russian immigrants to Israel, ex amining the relations between demands of immigration and depres sion, did not find any moderating resilience factors (Aroian & Norris, 2000). Future research should use other resilience factors to further explore these possibilities.…”
Section: Discussionmentioning
confidence: 67%
“…Nonetheless, the interaction hy pothesis regarding resilience factors was not confirmed and all of the interactions, with one exception, were not significant. Similarly, a previous study conducted among Russian immigrants to Israel, ex amining the relations between demands of immigration and depres sion, did not find any moderating resilience factors (Aroian & Norris, 2000). Future research should use other resilience factors to further explore these possibilities.…”
Section: Discussionmentioning
confidence: 67%
“…Besides examining the correlation of RS and self-rated health, we did not further examine the validity of the scale, but this has been done on numerous studies by finding significant correlations with psychological outcomes (Aroian & Norris, 2000;Heilemann et al, 2003;Humphreys, 2003;Nishi et al, 2010). However, one study (Aroian & Norris, 2000) has also suggested that resilience does not modify or mediate the relationship between the demands of immigration and depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study (Aroian & Norris, 2000) has also suggested that resilience does not modify or mediate the relationship between the demands of immigration and depression. Thus, further knowledge about the resilience and the processes by which it is connected with quality of life are needed.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on resilience in older populations and specifically older Holocaust survivors (Aroian & Norris, 2000;Felton, 2000;Kahana, 1992;Lamet & Dyer, 2004;Masten, 2001;Wagnild, 2003). Kahana and Felton's studies both supported the notion that prior experience with trauma has an inoculating effect that leads to greater resilience in dealing with other forms of stress.…”
Section: Discussionmentioning
confidence: 99%